My mindful walk with Grandma - Mabry, Sheri (Albert Whitman & Company, 2020)
When a girl walks through the woods with her Grandma, she is so excited about their destination that she misses out on what is around her, but with Grandma's help, she learns how to breathe, be peaceful, and find herself in nature.